2003
DOI: 10.1007/s00432-003-0433-y
|View full text |Cite
|
Sign up to set email alerts
|

Growth-promoting effect of muscarinic acetylcholine receptors in colon cancer cells

Abstract: Purpose: G-protein-coupled receptors are known to mediate cell growth via divergent signaling pathways. It has been reported that colon cancer cells express muscarinic acetylcholine receptor (mAChR) although their functional role is largely unknown. The aim of this study is to elucidate possible mechanisms responsible for the growth-promoting effect of mAChRs in colon cancer cells by using colon cancer cell line T84. Methods: Carbachol, a stable mAChR agonist, dose-dependently induced cell growth with a maxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 39 publications
3
22
1
Order By: Relevance
“…Follow-up studies by Frucht and co-workers (Frucht et al 1999; Yang and Frucht 2000) demonstrated that the receptors were primarily M3, were increased approximately eightfold in tumor versus normal, and that carbamylcholine stimulated proliferation of colon carcinoma cell lines expressing M3 receptors. Raufman et al (2003) and Ukegawa et al (2003) confirmed those findings, again showing the importance of M3 receptors and also demonstrated that the proliferative action of M3 receptors depended in part on the transactivation of EGF receptors. The actual role of M3 receptors in colon cancer development was further confirmed by Raufman et al (2008) who showed that M3 receptor knockout mice were resistant to the development of colon tumors in the azoxymethane-induced colon neoplasia model.…”
Section: Muscarinic Receptors and Specific Cancerssupporting
confidence: 73%
“…Follow-up studies by Frucht and co-workers (Frucht et al 1999; Yang and Frucht 2000) demonstrated that the receptors were primarily M3, were increased approximately eightfold in tumor versus normal, and that carbamylcholine stimulated proliferation of colon carcinoma cell lines expressing M3 receptors. Raufman et al (2003) and Ukegawa et al (2003) confirmed those findings, again showing the importance of M3 receptors and also demonstrated that the proliferative action of M3 receptors depended in part on the transactivation of EGF receptors. The actual role of M3 receptors in colon cancer development was further confirmed by Raufman et al (2008) who showed that M3 receptor knockout mice were resistant to the development of colon tumors in the azoxymethane-induced colon neoplasia model.…”
Section: Muscarinic Receptors and Specific Cancerssupporting
confidence: 73%
“…Whereas work from our [19] and other groups [2-4,7,8] provide strong evidence that M3R acts as a tumor promoter, the present observations newly suggest that in the colon M1R acts as a tumor suppressor. This putative role for M1R is unmasked by combined M1R and M3R deficiency in dual KO mice where tumor formation is similar to that observed in WT mice.…”
Section: Discussioncontrasting
confidence: 50%
“…Activation of muscarinic receptors and downstream signaling was shown to stimulate proliferation of cells derived from lung [1,2], breast [3,4], prostate [5], colon [6,7], and skin [8] cancers, and muscarinic receptors are frequently over-expressed in these common cancers [9]. Hence, it is highly likely that activation of muscarinic receptor signaling plays a fundamentally important role in neoplastic transformation and progression.…”
Section: Introductionmentioning
confidence: 99%
“…Frucht et al (1999) demonstrated that the M3 expression was increased about eight-fold in tumor versus normal tissue, and that the cholinergic agonist carbamylcholine stimulated the proliferation of M3-expressing colon carcinoma cell lines (Yang and Frucht, 2000). These findings were confirmed by other research groups, who demonstrated that the proliferative action of the M3 receptors depended partially on the trans- activation of epithelial growth factor (EGF) receptors (Raufman et al, 2003; Ukegawa et al, 2003). Later, it was shown that the M3 receptor knockout mice were resistant to the development of colon tumors in the azoxymethane-induced colon neoplasia model (Raufman et al, 2008).…”
Section: Cholinergic Signaling May Be Involved In T Leukemogenesissupporting
confidence: 78%